THE EFFECTS OF TOKEN ECONOMY REINFORCEMENT ON SELF - DISCIPLINE OF PRESCHOOL CHILDREN IN SCHOOLS UNDER SURAT THANI PRIMARY EDUCATION SERVICE AREA OFFICE 2 - Buhngo, Kanchana; Meesomsarn, Kantawan; Jearakul, Praphon (Journal of MCU Nakhondhat, 2021)
The objectives of this research article were to 1) to study the development of self - discipline of preschool children while they were receiving token economy reinforcement; 2) to compare the levels of self - discipline of preschool children before and after receiving token economy reinforcement; and 3) to compare the levels of self - discipline of preschool children after receiving token economy reinforcement and during the follow - up period;. The research sample consisted of 18 female and male preschool children, aged 5 - 6 years, who were studying in the third year kindergarten level during the first semester of the 2019 academic year at Wat Sutthawas School, Chaiya district, Surat Thani province under Surat Thani Primary Education Service Area Office 2, obtained by cluster sampling. The employed research instruments were 1) a questionnaire on the need for reinforcement of preschool children; 2) a form for recording the rate of receiving token economy for preschool children; and 3) an observation form on self - discipline behavior of preschool children. Statistics for data analysis were the mean, standard deviation, and the Wilcoxon signed rank test. The research findings showed that 1) the preschool children who received reinforcement with token economy had higher development level of self - discipline; 2) after being reinforced with token economy, the preschool children’s mean score of self - discipline behavior was higher than their counterpart mean score before receiving token economy reinforcement at the .05 level of statistical significance; and 3) significant difference at the .05 level of statistical significance was found between the preschool children’s mean score of self - discipline behavior after being reinforced with token economy and their counterpart mean score during the follow - up period.